Autoantibody Profiling in a Cohort of Pediatric and Adult Patients With Autoimmune Hepatitis. Issue 1 (19th September 2014) - Villalta, Danilo; Girolami, Elia; Alessio, Maria Grazia; Sorrentino, Maria Concetta; Tampoia, Marilina; Brusca, Ignazio; Daves, Massimo; Porcelli, Brunetta; Barberio, Giuseppina; Conte, Mariaelisabetta; Pantarotto, Lisa; Bizzaro, Nicola; et al.
Abstract : Background: Autoimmune hepatitis (AIH) is a rare condition characterized by the presence of autoantibodies distinctive of type 1 AIH (AIH‐1) and type 2 AIH (AIH‐2). The aim of this study was to evaluate the autoantibody profile in a cohort of pediatric and adult AIH patients, using both indirect immunofluorescence (IIF) and a new multiplexed line‐blot assay. Methods: Sera from 63 pediatric and 53 adult AIH patients were tested for antinuclear (ANA), antismooth muscle (SMA), anti‐liver kidney microsome 1 (anti‐LKM1), anti‐liver cytosol 1 (anti‐LC1) autoantibodies using IIF methods; for anti‐LKM1, anti‐LC1, and soluble liver antigen/liver‐pancreas (anti‐SLA/LP) autoantibodies using the line‐blot; for anti‐F‐actin autoantibodies using IIF both on VSM47 cell‐line and on rat intestinal epithelial cells. Results: AIH‐1 was the most common type of AIH in the adult cohort (73.6%), while AIH‐2 was the most common AIH in the pediatric cohort (61.9%). Both in adult and pediatric AIH‐2 anti‐LKM1 were the prevalent autoantibodies. In pediatric AIH‐2 anti‐LC1 autoantibodies were more frequent than in adult AIH‐2 (59 vs. 28.6%), and in 35.9% of cases they were present alone. In 17 patients anti‐LC1 autoantibodies were detected only with the line‐blot assay. The levels of anti‐LKM1 and of anti‐LC1 were not different between adult and pediatric AIH, and the overall agreement between the results obtained with the two IIF methods for F‐actin detection was 98.8% (CI 95%: 94.4–99.7%). Conclusions: The line‐blot assay showed a higher sensitivity than IIF for anti‐LC1 detection. Anti‐LKM1 and anti‐LC1 autoantibody levels are not different in adults and children. An almost perfect agreement between the two IIF methods for anti‐F‐actin detection has been observed.